Syzygium aromaticum extract mediated, sustainable silver nanoparticle synergetic with heterocyclic antibiotic clarithromycin and their antimicrobial activities - Edis, Zehra; Haj Bloukh, Samir; Ashames, Akram A.; Al-Tabakha, Moawia M.; Shahwan, Moyad J. S. A.; Abu Sara, Hamed; Boddu, Sai H. S.; Khan, Sohaib N.; Bloukh, Ibrahim Haj; Eladdasy, Maram; Sadeghi, Somayeh; Alkubaisi, Haneen; et al. (Frontiers in Chemistry, 2025)
Microorganisms are becoming resistant to drugs and antimicrobials, making it a significantly critical global issue. Nosocomial infections are resulting in alarmingly increasing rates of morbidity and mortality. Plant derived compounds hold numerous antimicrobial properties, making them a very capable source to counteract resistant microbial strains. Syzygium aromaticum (Clove) extract has been proven by studies to contain active ingredients that demonstrate antibacterial, antifungal, antioxidant, and insecticidal properties. It has also been used historically for its pain relief especially for tooth ache. Clove extract derived nanoparticle synthesis is a promising method of combining therapeutics with metals at nanoscale. Such nanostructured systems in combination with the heterocyclic antibiotic clarithromycin could potentiate the action of plant extracts, decrease drug side effects and improve antimicrobial activity. In this study, clove extract (C) was successfully used to synthesize silver nanoparticles (AgNP) to create AgNPC and AgNPCA (A = clarithromycin). The two compounds underwent different analytical methods consisting of SEM, EDS, DLS, UV-vis, FTIR and XRD. These nanoparticles were used against a variety of 10 pathogens and exhibited very good to intermediate antibacterial properties. AgNPC resulted in better antibacterial properties and smaller nanoparticle size. This study demonstrates the potential of clove extract mediated AgNP synthesis in combination with and without the antibiotic clarithromycin.